Tracking Formation and Transport of Apollo 16 Lunar Impact Glasses through Chemistry and Dating - Hui, S.; Norman, M.; Jourdan, Fred (National Space Society of Australia Ltd, 2010)
Major and trace element analyses of 134 lunar impact spherules from a sample of Apollo 16 regolith (66031,65) have been completed. Thirty spherules were selected for radioisotopic dating using the 40Ar/39Ar method, 27 of these are derived from local soil based on the major and trace element compositions and the remainder have compositions exotic to the Apollo 16 landing site. Twenty-two of the dated spherules gave statistically acceptable 40Ar/39Arisochrons and plateaus, allowing us to develop the first impact flux for local impact spherules at the Apollo 16 site complementing previous work at Apollo 12 and 14. Our impact flux shows a recent (0-800 Ma) spike similar to that observed previously in Apollo 12 spherules. This suggests a recent influx of impactors but may also be an artefact of regolith processes.The method developed for this study has advantages over previous studies as it allows us to tie the major and trace chemistry with the age of a single spherule. This additional resolution allows us to determine contributions to the impact flux from exotic events and identify groups of impact spherules related to a single impact. Our results show that 13-17 unique impact events may have produced the spherule population at this site, depending on how the groups are identified. This approach has the potential to suppress apparent peaks on the impact age distribution and increase the apparent contribution of spherules from exotic sites.